PENETAPAN KADAR ASAM BENZOAT DALAM BEBERAPA MERK DAGANG MINUMAN RINGAN SECARA SPEKTROFOTOMETRI ULTRAVIOLET - Wahyu Irna Wati; Any Guntarti (Universitas Ahmad Dahlan, 2012)
Benzoic acid is one of the synthetic preservatives, work effectively at pH 2.5 to 4.0, therefore it is widely used in acidic food or drink. This study aims to determine benzoic acid content in some soft drink products, their conformity with Permenkes RI No.722/Menkes/Per/IX/88 on food additives, and to find out if there were any variance of benzoid acid content in a different kinds of soft drink products. Determination of benzoid acid levels was performed by ultraviolet spectrophotometry following solvent extraction of the benzoid acid with chloroform. Qualitatively, it was found that all of the sample contained benzoid acid. Quantitatively, the amount of benzoid acid in sample A was 227,73 mg/kg of materials; sample B was 182,38 mg/kg of materials; sampel C was 259,52 mg/kg of materials; sample D was 325,01 mg/kg of materials; sample E was 357,33 mg/kg of material. The result indicated that there were variance of benzoid acid content in different soft drink products. The use of benzoic acid in soft drinks was lower compaired to that of Permenkes RI No.722/Menkes/Per/IX/88 (600 mg/kg of materials).